2004
DOI: 10.1039/b315509a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and theoretical study of the redox properties of transition metal complexes with {Pt2S2} cores

Abstract: The oxidation processes undergone by the [Pt2(mu-S)2] core in [Pt2(P[intersection]P)2(mu-S)2](P[intersection]P = Ph2P(CH2)nPPh2, n= 2,3) complexes have been analysed on the basis of electrochemical measurements. The experimental results are indicative of two consecutive monoelectronic oxidations after which the [Pt2(mu-S)2] core evolves into [Pt2(mu-S2)]2+, containing a bridging disulfide ligand. However, the instability of the monoxidised [Pt2(P[intersection]P)2(mu-S)2]+ species formed initially, which conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…From this orbital analysis it can be inferred that a high electron density is located on the bridging chalcogenide ligand, which will thus be responsible for the nucleophilic character of [L 2 Pt(µ-X) 2 PtL 2 ] compounds. The energy of [25] These energy values are consistent with the lower oxidation potentials found for {Pt 2 Te 2 } than for {Pt 2 S 2 } containing complexes.…”
Section: Molecular and Electronic Structuressupporting
confidence: 89%
See 2 more Smart Citations
“…From this orbital analysis it can be inferred that a high electron density is located on the bridging chalcogenide ligand, which will thus be responsible for the nucleophilic character of [L 2 Pt(µ-X) 2 PtL 2 ] compounds. The energy of [25] These energy values are consistent with the lower oxidation potentials found for {Pt 2 Te 2 } than for {Pt 2 S 2 } containing complexes.…”
Section: Molecular and Electronic Structuressupporting
confidence: 89%
“…[25,26] Thus, DFT calculations for model complexes using simplified terminal phosphane ligands have revealed that in all cases the highest energy occupied molecular orbital (HOMO) consists of an antibonding combination of the chalcogen p π orbitals (p z ). A 3-D plot of this molecular orbital calculated for the model compound [(PH 3 ) 2 Pt(µ-S) 2 Pt(PH 3 ) 2 ] is shown in Figure 2.…”
Section: Molecular and Electronic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin the survey with inorganic compounds. Recent computations of standard reduction potentials include studies of aqueous metal ions, 268,301,304,305,308,321,322,[342][343][344][345] inorganic clusters containing sulfur and iron in different oxidation states, 346,347 systems of various complexity with the Pt 2 X 2 (X = chalcogenide) cores, 348 and the MFe 2 S 4 clusters (M = Mn, Fe, Co, Ni, Cu, Zn, and Mo) in water by testing four different exchange-correlation functionals (B3LYP, BP86, TPSS, and TPSSh) and the COSMO implicit-solvent model. 349 Houk and co-workers 350,351 computed the standard redox potentials of 36 nitrogen oxides and related species in water using a complete basis set extrapolation method (CBS-QB3) for gas-phase free energies and the PCM implicit-solvent model for solvation free energies with use of the Born-Haber thermochemical cycle (Scheme 2).…”
Section: Applicationsmentioning
confidence: 99%
“…Dinuclear platinum(II) sulfide complex [Pt 2 (μ-S) 2 (PPh 3 ) 4 ] 1a [ 1 ] and analogues with alternative phosphine [ 2,3 ] or arsine [ 4 ] ligands have been extensively investigated over a considerable length of time [ 5 ] because of the rich and diverse chemistry they display. Reactivity includes alkylation [ 6,7 ] and arylation [ 8,9 ] reactions (generating platinum-thiolate complexes), redox chemistry [ 10,11 ], metalloligand chemistry (whereupon one or both sulfide ligands coordinate to metal centres generating sulfide-bridged homo- [ 12 ] and hetero- [ 13 ] metallic aggregates), and interesting ligandbased reactivity [ 14 ].…”
mentioning
confidence: 99%